The book on how to make all the colour paints for illuminating books: unravelling a Portuguese Hebrew illuminators’ manual - Melo, Maria J. (2019)
These studies were supported by the Portuguese Science Foundation through three research projects and three Ph.D. grants, including the three awarded to Rita Castro, Paula Nabais and Tatiana Vitorino (Ph.D. Grant Nos. SFRH/BD/76789/2011, CORES Ph.D. programme PD/00253/2012: PD/BD/105895/2014 and PD/BD/105902/2014), and through the scientific infrastructures funded through RECI/QEQ-MED/0330/2012, REM2013 and the Associated Laboratory for Sustainable Chemistry—Clean Processes and Technologies—LAQV, which is financed by national funds from FCT/MEC (UID/QUI/50006/2015) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265).